2010
DOI: 10.1258/ebm.2009.009162
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative alterations inducedin vitroby the photodynamic reaction in doxorubicin-sensitive (LoVo) and -resistant (LoVoDX) colon adenocarcinoma cells

Abstract: In photodynamic therapy (PDT) a tumor-selective photosensitizer is administered and then activated by exposure to a light source of appropriate wavelength. Multidrug resistance (MDR) is largely caused by the drug efflux from the tumor cell by means of P-glycoprotein, resulting in reduced efficacy of the anticancer therapy. This study deals with photodynamic therapy with Photofrin (Ph) on colon cancer cell lines (doxorubicin-sensitive and -resistant). The cells were treated with 15 and 30 microg/mL Ph and then … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…The concept of Photofrin-mediated PDT enhanced with EP has not been studied yet; however, there are many studies on Photofrin-mediated PDT (Hajri et al 2002; Luo et al 2010; Tong et al 2000; Chang et al 2008; Korbelik and Krosl 1996; Henderson et al 2000; Schweitzer 2001; Jiang et al 1998; Kulbacka et al 2010). Several studies on Photofrin transport and accumulation mechanism were also conducted.…”
Section: Introductionmentioning
confidence: 99%
“…The concept of Photofrin-mediated PDT enhanced with EP has not been studied yet; however, there are many studies on Photofrin-mediated PDT (Hajri et al 2002; Luo et al 2010; Tong et al 2000; Chang et al 2008; Korbelik and Krosl 1996; Henderson et al 2000; Schweitzer 2001; Jiang et al 1998; Kulbacka et al 2010). Several studies on Photofrin transport and accumulation mechanism were also conducted.…”
Section: Introductionmentioning
confidence: 99%
“…We tested the effects of EP-mediated transport enhancement of the photosensitizer on cellular phototoxicity. The electric field, when selected appropriately, significantly increases the molecular transport of a drug and its intracellular concentration, with no significant destruction of the cell [26]. The EPDT applied in the amelanotic melanoma cells in vitro led to a five-fold increase in the cytotoxic effect and a more than 3.5-fold increase in cytotoxicity for the melanotic melanoma cells.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a significantly shorter exposure time (1 h instead of 4 h) was sufficient for the effect. The reduced exposure time is a characteristic advantage of enhancing PDT with EP [26]. The previous in-vitro melanoma study showed that PDT-based Photofrin is effective even without EP, but a much longer duration of incubation of Photofrin should be applied [18,19,21,34].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Determination of the effect of the environment on test compounds is essential in photodynamic therapy process. This allows to predict how the photosensitizer will behave in contact with other compounds in the cell [14,15].…”
Section: Introductionmentioning
confidence: 99%